Evaluation of respiratory movement during gated radiotherapy using film and electronic portal imaging - Ford, E.C; Mageras, G.S; Yorke, E; Rosenzweig, K.E; Wagman, R; Ling, C.C (International journal of radiation oncology, biology, physics, 2002)
Purpose : To evaluate the effectiveness of a commercial system 1 in reducing respiration-induced treatment uncertainty by gating the radiation delivery. 1 Varian Medical Systems, Inc., Palo Alto, CA. Methods and Materials : The gating system considered here measures respiration from the position of a reflective marker on the patient’s chest. Respiration-triggered planning CT scans were obtained for 8 patients (4 lung, 4 liver) at the intended phase of respiration (6 at end expiration and 2 at end inspiration). In addition, fluoroscopic movies were recorded simultaneously with the respiratory waveform. During the treatment sessions, gated localization films were used to measure the position of the diaphragm relative to the vertebral bodies, which was compared to the reference digitally reconstructed radiograph derived from the respiration-triggered planning CT. Variability was quantified by the standard deviation about the mean position. We also assessed the interfraction variability of soft tissue structures during gated treatment in 2 patients using an amorphous silicon electronic portal imaging device. Results : The gated localization films revealed an interfraction patient-averaged diaphragm variability of 2.8 ± 1.0 mm (error bars indicate standard deviation in the patient population). The fluoroscopic data yielded a patient-averaged intrafraction diaphragm variability of 2.6 ± 1.7 mm. With no gating, this intrafraction excursion became 6.9 ± 2.1 mm. In gated localization films, the patient-averaged mean displacement of the diaphragm from the planning position was 0.0 ± 3.9 mm. However, in 4 of the 8 patients, the mean (over localization films) displacement was >4 mm, indicating a systematic displacement in treatment position from the planned one. The position of soft tissue features observed in portal images during gated treatments over several fractions showed a mean variability between 2.6 and 5.7 mm. The intrafraction variability, however, was between 0.6 and 1.4 mm, indicating that most of the variability was due to patient setup errors rather than to respiratory motion. Conclusions : The gating system evaluated here reduces the intra- and interfraction variability of anatomy due to respiratory motion. However, systematic displacements were observed in some cases between the location of an anatomic feature at simulation and its location during treatment. Frequent monitoring is advisable with film or portal imaging.